TRANSFORMASI PEMBELAJARAN PBL DAN EDU CARD BERBASIS PUZZLE DI MAN 1 TUBAN: (Menyongsong Tantangan Berpikir Kritis di Era Digital) - Qolimin; Astuty, Henny Sri (ISTIQRA: Jurnal Hasil Penelitian, 2024)
This research aims to enhance students' critical thinking skills through the implementation of the problem-based learning (PBL) model. The study employs classroom action research conducted in class XI IPS 3 at MAN 1 Tuban, involving 30 students. Data collection methods include interviews, observations, documentation, and student response questionnaires. The results indicate a significant improvement in teacher activity and students' critical thinking skills. Teacher activity increased from 57% in the first cycle, 76% in the second cycle, to 93% in the third cycle, indicating very high effectiveness. Students' critical thinking skills also improved across all indicators, with scores of 42%, 67%, 39%, 42%, and 42% in the first cycle; 61%, 78%, 59%, 60%, and 60% in the second cycle; and 80%, 88%, 82%, 82%, and 84% in the third cycle. The positive response of students to PBL reached 92%, demonstrating a very high level of engagement. This study recommends the implementation of the PBL model in other schools in the Tuban District to enhance students' critical thinking skills.